DIGITALISASI MARKETING DALAM MENGEMBANGKAN POTENSI UMKM DI DESA JATIDROJOK KEDUNGPRING LAMONGAN - Ahmad Muthi’Uddin; Naning Kurniawati; Mahmud Samsuri (BHAKTI: JURNAL PENGABDIAN DAN PEMBERDAYAAN MASYARAKAT, 2025)
Digital Marketing is one of the marketing media trends that is currently in great demand by the public to support various activities. With E-Marketing, communications and transactions can be carried out at any time and can reach all corners of the world. Based on data taken from the Jatidrojog Village Community, the local residents have the majority of household businesses in the field of processed food production, such as crackers, tofu and snacks. The problems that UMKM still often encounter in running their business are related to HR, capital and marketing issues. The needs desired by the subject are digital marketing, such as WhatsApp business and creating a website as a means of branding, marketing and increasing product sales from the Jatidrojog Village UMKM community. Through this UMKM mentoring program, we have succeeded in making a real contribution to branding and digital product sales. In order to create economic prosperity for small communities. This is expected to provide social, economic, social harmony and environmental benefits.